Is rapid hepatitis C virus testing from corpses a screening option for index persons who have died after mass-casualty incidents in high-prevalence settings in the field?. Issue 3 (10th October 2013) - Hagen, Ralf M; Wulff, B; Loderstaedt, U; Fengler, I; Frickmann, H; Schwarz, N G; Polywka, S
Abstract : Introduction: We tested a commercially available rapid hepatitis C virus (HCV) test assay for its potential use for analyses of corpses as a screening option for index persons who have died after mass-casualty incidents in high-prevalence settings in the field. Materials and methods: 50 blood samples were drawn from 16 recently deceased confirmed HCV-positive patients whose corpses were stored at 4°C in the mortuary and were analysed at admission and up to 48 h post mortem by rapid serological testing using the ImmunoFlow HCV test (Core Diagnostics, Birmingham, UK) in comparison with automated serological assays and PCR. Samples from 50 HCV-negative corpses were also analysed. Results: The blood of only four of the 16 HCV-positive corpses reacted clearly with the ImmunoFlow HCV test, while in five cases the result was only weakly reactive and three cases showed very weak reactivity. Four of the infected corpses showed initially negative results, three of which became very weakly reactive 48 h post mortem. 49 out of 50 samples (98%) from HCV-negative corpses tested negative. Discussion: The rapid test system we investigated showed insufficient sensitivity regarding the identification of HCV positivity. Automated serological testing or PCR should be preferred if it is realistically available in the deployed military setting.